2018
DOI: 10.1016/j.jcis.2017.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of biocompatible and efficient antimicrobial porous polymer surfaces by the Breath Figures approach

Abstract: We designed and fabricated highly efficient and selective antibacterial substrates, i.e. surface non-cytotoxic against mammalian cells but exhibiting strong antibacterial activity. For that purpose, microporous substrates (pore sizes in the range of 3-5 m) were fabricated using the breath figures approach (BFs). These substrates have additionally a defined chemical composition in the pore cavity (herein either a poly(acrylic acid) or the antimicrobial peptide Nisin) while the composition of the rest of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…More recently, research efforts have been focused on either the use of natural compounds with anti-biofilm properties [14][15][16][17], or on the development of intrinsically antimicrobial and antifouling materials, by either physical or chemical technological approaches [17][18][19][20]. Physical approaches mainly consist of developing micro-or nano-scale surface texturing in order to affect bacterial adhesiveness, growth, and more in general, biofilm formation [21][22][23][24]. Chemical approaches, instead, mainly involve the functionalization of material surfaces, to meet some criteria that are well-recognized to confer repelling activities, which include strong hydrophilicity, neutral charge, and the presence of groups that are able to establish hydrogen bonds [25].Polyethylene glycol (PEG) is undoubtedly, the most closely investigated antifouling polymer, as it meets all of the criteria listed above [26].…”
mentioning
confidence: 99%
“…More recently, research efforts have been focused on either the use of natural compounds with anti-biofilm properties [14][15][16][17], or on the development of intrinsically antimicrobial and antifouling materials, by either physical or chemical technological approaches [17][18][19][20]. Physical approaches mainly consist of developing micro-or nano-scale surface texturing in order to affect bacterial adhesiveness, growth, and more in general, biofilm formation [21][22][23][24]. Chemical approaches, instead, mainly involve the functionalization of material surfaces, to meet some criteria that are well-recognized to confer repelling activities, which include strong hydrophilicity, neutral charge, and the presence of groups that are able to establish hydrogen bonds [25].Polyethylene glycol (PEG) is undoubtedly, the most closely investigated antifouling polymer, as it meets all of the criteria listed above [26].…”
mentioning
confidence: 99%
“…Moreover, the block length control in block. The blending of PS with poly(poly‐(ethylene glycol) methyl ether methacrylate), PS‐b‐PAA, and poly(N, N‐dimethylamino ethyl methacrylate) will result in a change of polymer matrix affecting the polymer films from the original PS film properties.…”
Section: Resultsmentioning
confidence: 99%
“…In these case, the block length in the block copolymers influence the solubility, dispersion, and therefore, controlling the length of the block are challenging drawback for the synthesis through tedious reaction conditions . In some cases, blending of polystyrene (PS) with polyethylene oxide (PEO) has been considered as a more convenient method to obtain the pore selective functionalization compared with using the block copolymers alone …”
Section: Introductionmentioning
confidence: 99%
“…By regulating the surface’s microstructure and adherence strength via pH-responsive changes, it is possible to fabricate switchable surfaces suitable for variable applications, like tissue engineering and drug/contaminant release/adsorption. Moreover, it has been demonstrated that PAAc presents antimicrobial properties against some antibiotic-resistant bacterial strains, often related to nosocomial infections [ 19 , 20 ]. Therefore, innovative material design approaches to achieve biologically active surfaces that prevent bacteria colonization are valuable in several biomedical-related fields [ 21 ].…”
Section: Introductionmentioning
confidence: 99%